Balanced scorecard management model in an educational institution's customer service - Martel-Carranza, Christian P. (2021)
Objective. To determine the effectiveness of the balanced scorecard management model in improving the quality of customer service at the Instituto de Educación Superior Tecnológico Privado Juan Bosco at Huánuco, 2020. Methods. The study had a quantitative, applied approach, with a quasi-experimental experimental design. The sample was non-probabilistic and consisted of 90 students, 45 for the control group and 45 for the experimental group, to whom a questionnaire with 40 items was applied at the beginning and end of the research work. The hypotheses were tested using Student's t-test. Results. It was evidenced that the application of the balanced scorecard model significantly improved the quality of customer service at the Institute, since in the related samples hypothesis test (pre- and post-test of the experimental group) the calculated t (tc = 4.51) is greater than the tabulated or critical t (tt = 1.68). The p-value of the mean difference was 0.000. Conclusions. The balanced scorecard management model significantly improves the quality of customer service at the Instituto Juan Bosco at Huánuco, since those who underwent the program obtained an improvement in customer service, compared to those who did not undergo the program and remained on average.